New 4H silicon carbide metal semiconductor field-effect transistor with a buffer layer between the gate and the channel layer - 张现军 杨银堂 段宝兴 陈斌 柴常春 宋坤 (Chinese physics B, 2012)
A new 4H silicon carbide metal semiconductor field-effect transistor （4H-SiC MESFET） structure with a buffer layer between the gate and the channel layer is proposed in this paper for high power microwave applications. The physics-based analytical models for calculating the performance of the proposed device are obtained by solving one- and two-dimensional Poisson＇s equations. In the models, we take into account not only two regions under the gate but also a third high field region between the gate and the drain which is usually omitted. The direct-current and the alternating- current performances for the proposed 4H-SiC MESFET with a buffer layer of 0.2 ~tm are calculated. The calculated results are in good agreement with the experimental data. The current is larger than that of the conventional structure. The cutoff frequency （fT） and the maximum oscillation frequency （fmax） are 20.4 GHz and 101.6 GHz, respectively, which are higher than 7.8 GHz and 45.3 GHz of the conventional structure. Therefore, the proposed 4H-SiC MESFET structure has better power and microwave performances than the conventional structure.